Infections in gynecology and obstetrics. Antibiotics in gynecology. - Gotuzzo Herencia, Eduardo (2015)
It is essential to stress the need for a proper diagnosis of bacterial infection; that is, take samples for Gram stains and cultures, in order to identify the pathogen, before starting treatment.